Some properties of a linear operator involving generalized Mittag-Leffler function - FRASIN, Basem Aref; AL-HAWARY, Tariq; YOUSEF, Feras (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
This paper introduces a new class Tγ ... (η) of analytic functions which is defined by means of a linear operator involving generalized Mittag-Leffler function H γ α,β,k (f ). The results investigated in this paper include, an inclusion relation for functions in the class T ; ;k() and also some subordination results of the linear operator H ; ;k(f). Several consequences of our results are also pointed out. Mathematics Subject Classification (2010): 33E12, 30C45.